2005
DOI: 10.1038/nature03248
|View full text |Cite
|
Sign up to set email alerts
|

Self-similarity of complex networks

Abstract: Complex networks have been studied extensively owing to their relevance to many real systems such as the world-wide web, the Internet, energy landscapes and biological and social networks. A large number of real networks are referred to as 'scale-free' because they show a power-law distribution of the number of links per node. However, it is widely believed that complex networks are not invariant or self-similar under a length-scale transformation. This conclusion originates from the 'small-world' property of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
1,197
2
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 1,358 publications
(1,268 citation statements)
references
References 15 publications
30
1,197
2
4
Order By: Relevance
“…b, A loop-like NON; P 1 is shown as a function of p for k = 6 and two values of q. The results are obtained using equation (19). Note that increasing q yields a first-order transition.…”
Section: Remark On Scale-free Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…b, A loop-like NON; P 1 is shown as a function of p for k = 6 and two values of q. The results are obtained using equation (19). Note that increasing q yields a first-order transition.…”
Section: Remark On Scale-free Networkmentioning
confidence: 99%
“…Dynamical processes, such as flow and electrical transport in heterogeneous networks, were shown to be significantly more efficient when compared with ErdAEs-Rényi networks 64,65 . Furthermore, it was shown that networks can also possess self-similar properties, so that under proper coarse graining (or, renormalization) of the nodes the network properties remain invariant 19 .However, these complex systems were mainly modelled and analysed as single networks that do not interact with or depend on other networks. In interacting networks, the failure of nodes in one network generally leads to the failure of dependent nodes in other networks, which in turn may cause further damage to the first network, leading to cascading failures and catastrophic consequences.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With the “sandpile model” and the “avalanche effect” as typical representation,43 exogenous‐endogenous collective dynamics may determine the next moment of an open system. As an important feature of system far‐from‐equilibrium (self‐organized criticality), self‐similarity has been proven to be the intrinsic property of complex network through the renormalization group theory 44. Interestingly, this property has also been extended to characterizing the community of the complex network 45.…”
Section: Discussionmentioning
confidence: 99%
“…Dybiec et al (2004) claim that it is impossible to stop epidemics on scale-free networks unless a large proportion of the population is treated. Others offer hope in identifying the most highly connected sites (hubs) as the most vulnerable part of such systems (Albert et al 2000;Callaway et al 2000;May & Lloyd 2001;Song et al 2005;Jeger et al 2007).…”
Section: Introductionmentioning
confidence: 99%